2005
DOI: 10.1002/isaf.262
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of machine‐learning classifiers for selecting money managers

Abstract: Machine‐learning algorithms have performed well on noisy datasets that are typical of financial data. This paper compares the performance of three types of machine‐learning classifier for selecting money managers. Naïve Bayes, neural network and decision tree learners were applied to a dataset of US equity managers. Although other studies have suggested that the performance of classifiers appears to be highly dependent on the nature of the problem and the dataset, the learning algorithms each had similar predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…ANN applications have been widely used for forecasting in a variety of areas [9], [11], [13], [16], [21]. ANN was used for the solution of numerous financial problems [9].…”
Section: Related Workmentioning
confidence: 99%
“…ANN applications have been widely used for forecasting in a variety of areas [9], [11], [13], [16], [21]. ANN was used for the solution of numerous financial problems [9].…”
Section: Related Workmentioning
confidence: 99%
“…-Decision Trees (DTs): Decision-tree learning is a symbolic induction method that produces syntactically simple, easily interpreted rules [11]. In DTs, the knowledge extracted from the given data is organized in a recursive hierarchical structure represented with the help of nodes and branches [12].…”
Section: -Machine Learning Approachesmentioning
confidence: 99%
“…Such studies prove that the nonlinear model presents more consistent results for stock exchange market. For this reason, ANN applications have been widely used in a variety of areas in financial markets [8], [9]. Reference [9] confirmed that ANN was used for the solution of numerous financial problems.…”
Section: Introductionmentioning
confidence: 98%